2020
DOI: 10.1088/1742-6596/1572/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Mineral identification of rocks from Pohon Batu hot springs in West Seram using FTIR spectroscopy

Abstract: This study demonstrates the Fourier Transform Infrared (FTIR) spectroscopy which has been applied to identification of mineral rocks from Pohon Batu hot springs, West Seram regency, Province of Maluku. FTIR spectroscopic interpretation are absorbance or transmittance spectra as a function of wavelength that shows the content of organic compounds found in rocks. From the conditions of mineral formation and presence of various impurity ions and elements also influence the intensity and position of the IR absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Although DOM accounts for a small proportion of the total organic matter (NRM: 1.7%; NRI: 1.9%; RM: 2.2%; RI: 2.5%), as the most active component of SOM, it can chelate heavy metals, thus changing their activities and influencing their migration and transformation. This study showed that intercropping increased the content of DOM compared to monocropping, which is consistent with the findings of other studies [36,37]. The DOM acts as a substrate for microorganisms to synthesize and promote organic matter with stability [38] and can significantly improve the extractability and availability of metals, thereby enhancing their absorption by bamboo.…”
Section: The Contents Of Som and Domsupporting
confidence: 91%
“…Although DOM accounts for a small proportion of the total organic matter (NRM: 1.7%; NRI: 1.9%; RM: 2.2%; RI: 2.5%), as the most active component of SOM, it can chelate heavy metals, thus changing their activities and influencing their migration and transformation. This study showed that intercropping increased the content of DOM compared to monocropping, which is consistent with the findings of other studies [36,37]. The DOM acts as a substrate for microorganisms to synthesize and promote organic matter with stability [38] and can significantly improve the extractability and availability of metals, thereby enhancing their absorption by bamboo.…”
Section: The Contents Of Som and Domsupporting
confidence: 91%